Prevalence of Risk Factors of Major NonCommunicable Diseases among Adolescents of Higher Secondary Schools of Kaski, District - Yadav, Dipendra Kumar; Sharma, Bhoopendra; Shrestha, Naveen; Karmacharya, Isha; Yadav, Saroj (Journal of Nepal Health Research Council, 2018)
Background: The main aim of this study is to determine the prevalence of major Non communicable disease risk factors among higher secondary school students. Methods: A cross-sectional study was conducted among higher secondary students of grade 11 and 12 of Kaski district in Nepal. The study period was from July 2016 to June 2017. Total sample 640 higher secondary students were recruited through two-stage cluster sampling. Self-administrated questionnaire was used for the data collection tool along with other tools which were used such as UNICEF electronic weighing scale, stature meter and mechanical aneroid sphygmomanometer. Ethical approval was obtained from IRC, Pokhara University. Data were entered into EpiData software and analysis was performed with the help of the Statistical Package for Social Science (SPSS). Results: The prevalence of smoking was 6.1% which was high in male (11.9%) than female (0.6%). Alcohol consumption practice among the adolescents was 18.9%. Family history of hypertension was seen higher than family history of diabetes.The prevalence of hypertension was 11.7%.High prevalence of abnormal values of systolic and diastolic BP was found in male than female students. Overweight was seen in 6.1% students. Prevalence of obesity was almost equal in both groups. Conclusions: There is high prevalence of smoking, alcoholism among adolescents. Hypertension was more common than diabetes among adolescents.